Pertussis Disease, Control and Challenges - Dias, Waldely; Raw, Isaias (IntechOpen, 2018)
In this book, we propose some approaches about interrelationships between vaccine strategies and microbial epidemiology, taking into account as reference the whooping cough, an endemic disease with significant morbidity and mortality and of indisputable importance in public health.